Alter ego [videorecording (DVD)] - Walsh, Dylan; Stanulis, Steve; Roberts, Eric, 1956-; Twiss, Deborah (Indican Pictures, 2022)
This is a story of a reclusive paranoia genius author who spends a night in his isolated mansion waiting for his creation to come and destroy him.